Suspects' Rights to Demand Compensation for Unlawful Detention at Cirebon Police Station - Febriyanto, Zefri (Ann Publisher, 2024)
Law enforcement is one of the efforts to achieve or create order, security, and tranquility in society, both as an effort to prevent and eradicate or enforce a violation of the law. Criminal offense is a term derived from the Dutch translation of strafbaarfeit. The word strafbaarfeit was later translated into various languages in Indonesian. Some words used to translate strafbaarfeit by scholars in Indonesia include criminal acts, delicacies, and criminal acts. The type of research the author uses is descriptive writing, which provides data that is as thorough as possible about humans, conditions, or other symptoms. The point is to reinforce the hypothesis to help strengthen the old theory or within the framework of compiling new theories. The results of this study showed that in 2017, there was one pretrial application, and the judge's decision showed that it was not granted, while in 2018, there was no pretrial application. In 2019, there were also no pretrial applications, while in 2020, there were two pretrial applications, and the judge's decision showed that one pretrial application was granted and one was not. Implementing the fulfillment of the rights of suspects demanding compensation for unlawful detention in Cirebon Regency has not been optimal.